(untitled) (Relevant Tomorrow / Aktualu rytoj, 2023)
It has become common practice for the contemporary art (institutional) system in Vilnius to hide ideology under allegories and metaphors. The aim of the article is to expose the dominant ideology in the Vilnius contemporary art system during the period of independence, highlighting the main markers of its change. To this end, the quasi-ideological preferences of the discourse of the Vilnius contemporary art (institutional) system are analyzed by using a study of Karl Mannheim’s and Michael Freeden’s on ideologies, as well as the studies of the post-communist transformation in Lithuania by Marius P. Šaulauskas and Zenonas Norkus. The research has shown that from 1992 to around 2010, in the environment of official conservative cultural policy, the Vilnius contemporary art (institutional) system and the discourse representing it has embodied (neo)liberal ideology. This was accomplished indirectly by avoiding open or using vague ideological rhetoric and expressing or disguising it in metaphors. Since 2010, a ‘conservative turn’ of the Vilnius contemporary art (institutional) system (discourse) can be observed as a consequence of the global conservative drift. The processes of ideological conservatism are not yet over; therefore, the change in the Vilnius contemporary art system after 2010 cannot yet be evaluated unequivocally.